New plasticising process for increased precision and reduced residence times in injection moulding of micro parts. (May 2015) - Hopmann, Ch.; Fischer, T.
Abstract: Plastic components for current applications in microsystems technology are becoming increasingly complex. At the same time the dimensions of these components decrease. A precise process control is essential for a constant high quality in injection moulding of these components. Since especially small shot weights can be difficult to realise with standard injection moulding, a series of special machines have been developed in the course of recent decades, which allow the processing of even the smallest amounts of melt in the milligram range. This paper describes the design, development and commissioning of an alternative plasticising unit for micro injection moulding. In the first step, the geometry of the so-called Inverse screw is designed and a test rig for plasticising trials is developed. After optimising the geometry based on experimental tests different concepts for non-return valves are designed and tested for their closing performance. Finally, the concept is transferred to a micro injection moulding machine and the applicability in practical investigations is demonstrated.